Changing prognostic significance of tumor stage and nodal stage in patients with squamous cell carcinoma of the oropharynx in the human papillomavirus era. Issue 15 (14th April 2015) - Keane, Florence K.; Chen, Yui‐Hui; Neville, Bridget A.; Tishler, Roy B.; Schoenfeld, Jonathan D.; Catalano, Paul J.; Margalit, Danielle N.
<x xml:space="preserve">Abstract</x> BACKGROUND Although human papillomavirus (HPV)–associated oropharyngeal squamous cell carcinoma (OPSCC) tends to present at an advanced nodal stage (N stage), the prognosis is generally better than that for HPV‐negative OPSCC. Prior work has demonstrated the increasing incidence of HPV‐related OPSCC in the United States. This study was designed to determine whether the changing epidemiology of OPSCC is reflected in changes in the prognostic significance of the tumor stage (T stage) and the N stage in a population‐based cohort. METHODS The Surveillance, Epidemiology, and End Results program was used to identify 13, 328 patients who were 18 years old or older and were diagnosed with OPSCC from 1997 to 2008. The Kaplan‐Meier method was used to estimate head and neck cancer–specific survival. Cox proportional hazards models were used to evaluate the associations between head and neck cancer–specific mortality (HNCSM) and T and N stages and the interaction of variables with the year of diagnosis. RESULTS With a median follow‐up of 67 months, there were 4099 head and neck cancer deaths. There was a significant interaction between the T stage and time (P for interaction = .01), with the effect of the T stage on HNCSM increasing from 1997 to 2008. The T stage retained a linear relationship with HNCSM. The effect of the N stage on HNCSM declined over time (P for interaction = .0004). The current American Joint Committee on Cancer (AJCC) staging system did not subdivide distinct prognostic subgroups for HNCSM by overall stage. CONCLUSIONS In this population‐based study of OPSCC, the effect of the N stage on cancer‐specific mortality decreased over time as the impact of the T stage increased. The current AJCC staging system did not distinguish prognostic subgroups. These changes may reflect the increasing prevalence of HPV‐related OPSCC. Further study in HPV‐defined cohorts is needed to tailor the AJCC staging system to better reflect HNCSM risk. Cancer 2015;121:2594–2602. © 2015 American Cancer Society.